(untitled) (Journal of Health, Population and Nutrition, 2009)
The existence of pockets of under-vaccinated persons has allowed outbreaks of disease in countries that have achieved high levels of vaccination coverage. A field-based methodology-GAPS (Geographic Assessment of Planning and Services)-was developed to predict, in advance of an immunization campaign, the sites of which are most likely to have a pocket of unvaccinated persons and then use this information to improve planning, supervision, and evaluation of the campaign. At this time, there have been two applications of GAPS (Nepal and Ethiopia). The purpose of this paper was to evaluate these two applications of GAPS and make recommendations regarding its future use. Structured, expert interviews were conducted with at least three campaign organizers to evaluate each application of GAPS using purposive sampling. An evaluation of an individual campaign was considered positive when at least two of the three campaign organizers considered GAPS to be useful and worthwhile. The three campaign organizers interviewed following the GAPS application in Ethiopia responded that GAPS was useful and worth the effort. In Nepal, all four campaign organizers responded that GAPS was useful and worth the effort. Some suggestions for improvement were also identified. Although this evaluation was limited in the number of applications evaluated, GAPS appears to have promise as a practical method to help improve the quality of mass immunization campaigns. And even if no pockets of unvaccinated persons are found, the method may serve as a rapid quality-check of administrative estimates of coverage. Further applications in different settings are needed to confirm these findings or under what circumstances GAPS might best be used. GAPS may also be considered for improving other types of health campaigns, such as distribution of insecticide-treated bednets, vitamin A capsules, and deworming medications. J Health Popul Nutr 2009 Oct; 27(5):684-695